Modulation of natriuretic peptide receptors in human adipose tissue: molecular mechanisms behind the “natriuretic handicap” in morbidly obese patients - Gentili, Alessandra; Frangione, Maria Rosaria; Albini, Elisa; Vacca, Carmine; Ricci, Maria Anastasia; De Vuono, Stefano; Boni, Marcello; Rondelli, Fabio; Rotelli, Luciana; Lupattelli, Graziana; Orabona, Ciriana (Translational research : the journal of laboratory and clinical medicine, 2017)
The B-type natriuretic peptide (BNP) hormone plays a crucial role in the regulation of cardiovascular and energy homeostasis. Obesity is associated with low circulating levels of BNP, a condition known as “natriuretic handicap.” Recent evidences suggest an altered expression of BNP receptors—both the signaling natriuretic peptide receptors (NPR)-A and the clearance NPR-C receptor—in adipose tissue (AT) as one of the putative causes of natriuretic handicap. The current study aims at clarifying the molecular mechanisms behind the natriuretic handicap, focusing on NPR modulation in the AT of obese and control subjects. The study enrolled 34 obese and 20 control subjects undergoing bariatric or abdominal surgery, respectively. The main clinical and biochemical parameters, including circulating BNP, were assessed. In visceral (VAT) and subcutaneous AT (SAT) samples, collected during surgery, the adipocytes and stromal vascular fraction (SVF) expression of NPR-A and NPR-C and the SVF secretion of interleukin 6 (IL-6) were determined. Both VAT and SAT from obese patients expressed a lower NPR-A/NPR-C ratio in adipocytes and the SVF secreted a higher level of IL-6, compared with the controls. Moreover, NPR-A/NPR-C ratio expressed by VAT and SAT adipocytes negatively correlated with body mass index, insulin, the Homeostasis Model Assessment of Insulin resistance, and IL-6 secreted by SVF, and the expression of the clearance receptor NPR-C, in both the VAT and SAT adipocytes, showed a negative correlation with circulating BNP. Overall, insulin resistance/hyperinsulinemia and AT inflammation (ie, high level of IL-6) are the major determinants of the lower NPR-A/NPR-C ratio in adipocytes, thus contributing to the natriuretic handicap in obese subjects.